How to build a resilient system - Zuo, En Qing. (2013)
With the population of computers and high-speed development of network, people manage to conduct activities on various areas by using network. The complex network is short of security and easy to be crashed under attacks because of its unique structure. Plenty of studies have shown that attacks on some important nodes of network cause huge damage. Hence, designing resilient networks has increasingly become an important issue.